Study of Exploratory Model about the Effects of Cognitive Abilities, Socio Emotional Competences in School Achievement - Candeias, A. A. (2014)
This study proposes to look for school achievment from children from primary school starting from the proposals of the ecological model (Bronfenbrenner, 1989; 1993), multidisciplinary approaches (Machado, Matias, & Leal, 2005) and sociocognitve approaches (Sternberg & Grigorenko, 2003; Kihlstrom & Cantor, 2000; Candeias, 2004). We use the most classical delimitation of school achievement based in PISA criteria (2006), namely achiement in the domains considered crucial by OEDC, maths, science and writing. The relationship between school achievment and cognitive functioning is strongly documented but the effects of social and emotional competences in school achievment are not enough studied. Despite the models about student interaction, as proposed by Ren and Arnold (2003) demonstrate the importance from cultural, economic, social and familiar factors in school achievment, as well as in attitudes toward school and learning, perceptions of competence and student motivation, specially the way that those factors interact in different levels, modeling the way students perceive him/herself and the environment surround him/he. Thus, we propose to explore how socio-emotional competences influences school achievment when we consider cognitive and contextual factors.